The Effect of Website-Based Education on Knowledge, Attitude and Compliance with Consumption of Blood Supplement Tablets in Adolescent Girls: Systematic Review - Hafidz Al Qodri; Tri Hartiti; Siti Aisah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Anemia is a significant global health issue, especially among adolescent girls, caused by insufficient iron intake needed for hemoglobin synthesis. This study aims to explore the impact of ePuskesmas-based detection methods and website-based EDUMA on knowledge and adherence to iron tablet consumption among adolescent girls in Indonesia, as an effort to reduce the prevalence of anemia. Method: This study employs a literature review methodology by searching scientific articles through Google Scholar, Proquest, and PubMed platforms. Inclusion criteria encompass quantitative and qualitative articles published between 2019-2024, focusing on the use of ePuskesmas and EDUMA to enhance knowledge and adherence to iron tablet consumption among adolescent girls. Results: Initial identification yielded 622 potential articles, from which 18 articles were selected after inclusion and exclusion criteria. These articles indicate that technology-based approaches, such as Android applications, web platforms, and adherence monitoring systems, are effective in improving knowledge and adherence of adolescent girls to iron tablet consumption. Conclusion: These findings affirm that the integration of information technology in healthcare systems, such as ePuskesmas and website-based EDUMA, can be an effective strategy to enhance understanding and adherence of adolescent girls to iron tablet consumption to address anemia.